High-transmittance anti-aging glass fiber reinforced polypropylene composite material and preparation method thereof
By adding modified nano zinc oxide, nano titanium dioxide and other components to polypropylene, combined with glass fiber and toughening agent, the problem of aging of polypropylene under ultraviolet irradiation is solved, and a composite material with high light transmittance and anti-aging properties is achieved, which is suitable for light-transmitting parts with large-size bearing capacity requirements.
Patent Information
- Application Number
- CN202411975011.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
AI Technical Summary
The existing light-transmitting polypropylene materials age under long-term ultraviolet irradiation, resulting in a decrease in light transmittance performance and insufficient toughness under low temperature conditions, making it difficult to meet the requirements of large-size bearing capacity.
High light-transmitting anti-aging glass fiber reinforced polypropylene composite material is used to improve the light transmittance and anti-aging properties of the material by adding modified nano zinc oxide and nano titanium dioxide, toughening agents, glass fibers and light stabilizers to the polypropylene.
It realizes the material's high light transmittance, good mechanical properties and significant anti-aging properties, and can be used effectively in direct sunlight. It is suitable for light-transmitting parts with large-size bearing capacity requirements.
Smart Images

Figure BDA0005220249900000061 
Figure BDA0005220249900000071 
Figure BDA0005220249900000072
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer material modification, and in particular to a high-light-transmittance and anti-aging glass fiber reinforced polypropylene composite material and a preparation method thereof. Background Art
[0002] Recently, the domestic automobile industry has developed rapidly and is also facing the transformation and upgrading of high-quality production. Polypropylene is widely used due to its advantages such as low density, low cost and easy processing. Under the market demand for intelligence and Internet, light transmittance requirements are put forward for interior and exterior decoration materials. Polypropylene is a semi-crystalline material, which has a certain degree of light transmittance. It has been used in automotive dashboard door panels and other ambient light parts and bumper surroundings.
[0003] Although polypropylene has certain strength and hardness, its toughness and low-temperature performance are poor. When used, it needs to be modified by filling minerals, glass fibers and other components, which will greatly reduce the light transmittance of the composite material. At present, the main light-transmitting materials used on the market are pure polypropylene. The performance of the material cannot meet the needs of a richer application scenario, and it is not applicable to parts with larger sizes and certain load-bearing requirements. During daily use of light-transmitting materials, long-term exposure to light and sunlight will accelerate the aging of polypropylene, especially ultraviolet rays will cut off the molecular chains of polypropylene and induce photo-oxidation reactions under the action of oxygen, seriously affecting the light transmittance of the material. CN202210782617.8 discloses a high-haze and high-transmittance polypropylene composition, a preparation method and application thereof, using nano-barium sulfate and nano-zinc oxide in combination with a β-nucleating agent to improve the transmittance and haze of the material. However, this method does not significantly improve the material performance and does not provide a clear conclusion on the light aging performance; 202011292440.0 discloses a highly light-transmitting polypropylene material that is resistant to long-term thermal oxidation aging and a preparation method thereof, which utilizes syndiotactic polypropylene and a compounded antioxidant in combination with a metal ion passivator. This patent focuses on improving the material's anti-aging ability, and does not significantly improve performance and transmittance. 202410052634.5 discloses a light-transmitting polypropylene composite and its preparation method and application, which uses anhydrous calcium sulfate whiskers as a light diffuser, and a compound of hindered phenols and thioether antioxidants, and is combined with a UV absorber to improve the material's resistance to light aging. This patent mainly targets aging resistance, and the material's transmittance and mechanical properties have not been significantly improved, and its application areas are limited. Summary of the invention
[0004] In order to solve the above problems, the purpose of the present invention is to provide a high-transmittance and anti-aging glass fiber reinforced polypropylene composite material and a preparation method and application thereof.
[0005] The present invention provides a high-transmittance and anti-aging glass fiber reinforced polypropylene composite material, comprising the following raw materials in parts by weight:
[0006] Polypropylene: 20-60wt%;
[0007] Toughening agent: 10-15wt%;
[0008] Glass fiber: 5-20wt%;
[0009] Nucleating agent: 0.3-1wt%;
[0010] Modified nano zinc oxide masterbatch: 10-20wt%;
[0011] Modified nano titanium dioxide masterbatch: 1-5wt%;
[0012] Maleic anhydride: 2-5wt%;
[0013] Antioxidant: 0.01-0.5wt%;
[0014] Light stabilizer: 0.01-0.5wt%;
[0015] Other additives: 1-5wt%.
[0016] One embodiment of the present invention,
[0017] The polypropylene is selected from one or more of homopolymer polypropylene and random copolymer polypropylene; the addition of ethylene monomer makes the molecular chain of polypropylene softer and more transparent, destroys the regular arrangement of the molecular chain of polypropylene, reduces the crystallinity and improves the light transmittance.
[0018] The melt flow rate of the homopolymer polypropylene is 20-60 g / 10 min at 230° C. and 2.16 kg, and the transmittance at 3.2 mm is ≥60%; the melt flow rate of the random copolymer polypropylene is 30-90 g / 10 min at 230° C. and 2.16 kg, and the transmittance at 3.2 mm is ≥70%.
[0019] The toughening agent is a transparent styrene-ethylene-butylene-styrene block copolymer, with a GPC weight average molecular weight Mw≤130000 g / mol, a melt flow rate of 1-30 g / 10 min at 230° C. and 5 kg, and a styrene content of 10-30 wt %. Styrene-ethylene-butylene-styrene itself has good transparency and compatibility with polypropylene, and has little effect on the light transmittance of the material.
[0020] The nucleating agent is one or more α-nucleating agents; the α-nucleating agent can accelerate the crystallization rate of PP, avoid the formation of large-sized spherulites of PP, reduce the size of crystal spheres, and thus reduce the reflectivity of PP materials, thereby improving the light transmittance of the materials. The reduction of crystal areas can also increase the transmittance of visible light and reduce light loss.
[0021] The glass fiber is Taishan glass fiber T438G, with a single filament diameter of 13 μm and a refractive index of 1.49-1.51, which is close to the refractive index of PP (1.48-1.50). When light enters the material, it will be refracted at the interface between the medium and the material and between the components. In a multi-component system, the closer the refractive index of each component is, the less the light transmission loss is and the higher the transmittance is.
[0022] The antioxidant is one or more of hindered phenols, phosphites and thiosulfates, preferably antioxidant 1010 (tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol) and antioxidant 168 (tris(2,4-di-tert-butylphenyl)phosphite);
[0023] The light stabilizer is a mixture of hindered amine and triazine ultraviolet absorbers; hindered amine ultraviolet absorbers can capture free radicals to reduce the speed of light initiation and chain growth in the photooxidation mechanism, thereby preventing or delaying the photodegradation process. Triazine ultraviolet absorbers mainly convert the absorbed ultraviolet rays into harmless energy and release them.
[0024] The lubricant is a stearate, such as zinc stearate, calcium stearate, vinyl bisstearamide, etc.;
[0025] The nano zinc oxide masterbatch comprises the following raw materials by weight: modified nano zinc oxide: 30wt%; lubricant: 0.1-2wt%;
[0026] Antioxidant: 0.01-0.5wt%; Polypropylene: the remaining components; The production steps of the nano zinc oxide masterbatch are as follows: weigh the modified nano zinc oxide, lubricant and polypropylene according to the above mass ratio, put the weighed materials into a high-speed mixer for uniform mixing; melt extrusion through a twin-screw extruder, underwater pelletization and drying to obtain the nano zinc oxide masterbatch. The temperature of each zone of the twin-screw extruder is 200-230°C, and the main engine speed is 300-400rpm.
[0027] The particle size of the nano zinc oxide is 60-80nm; when the filler particle size is below 100nm, the particles can reduce the scattering of light, making it easier for light to pass through the material, and have no significant effect on the light transmittance of the material.
[0028] The modification steps of the nano zinc oxide are as follows:
[0029] Place nano zinc oxide in a dried beaker, mix anhydrous ethanol and deionized water in a mass ratio of 3:5, then add the mixture to the beaker, ultrasonically disperse for 30 minutes, stir with a magnetic stirrer for 1-2 hours, and rotate at 1000r / min. After the temperature is constant (50-60℃), gradually add silane coupling agent to the beaker, cool to room temperature after the reaction, wash the obtained solution, centrifuge to remove impurities, and dry to obtain modified nano zinc oxide; the nano titanium dioxide particle size is 10-30nm; its particle size range is smaller than that of nano zinc oxide, which can well play the size complementary effect and improve the internal defects of nano zinc oxide. Its smaller size and trace addition will not reduce the light transmittance of the material.
[0030] The nano titanium dioxide masterbatch comprises the following raw materials by weight: nano titanium dioxide: 10wt%; lubricant: 0.1-2wt%;
[0031] Antioxidant: 0.01-0.5wt%; Polypropylene: remaining components; The production steps of the nano titanium dioxide masterbatch are as follows: put the nano titanium dioxide in a dried beaker, mix anhydrous ethanol and deionized water in a mass ratio of 2:3, then add the mixed solution into the beaker, ultrasonically disperse for 20 minutes, and then stir with a magnetic stirrer for 1 hour at a speed of 1000r / min. After the temperature is constant, gradually add a silane coupling agent (5%-10%) to the beaker, cool to room temperature after the reaction is completed, wash the obtained solution, centrifuge to remove impurities, and dry to obtain modified nano titanium dioxide.
[0032] The modified nano titanium dioxide is mixed with lubricant, antioxidant and polypropylene according to the above mass ratio, and the weighed materials are put into a high-speed mixer for uniform mixing; then melt-extruded by a twin-screw extruder, pelletized underwater and dried to obtain nano zinc oxide masterbatch. The temperature of each zone of the twin-screw extruder is 200-230°C, and the main engine speed is 300-400rpm.
[0033] The production steps of the high light transmittance and anti-aging glass fiber reinforced polypropylene composite material are as follows:
[0034] Weigh polypropylene, nano zinc oxide masterbatch, nano titanium dioxide masterbatch, toughening agent, antioxidant, light stabilizer, and other additives according to the weight ratio, put the weighed materials into a high-speed mixer and mix them evenly, and then add them to the main feeding port of the twin-screw extruder;
[0035] The glass fiber is weighed according to the ratio, and then added to a twin-screw extruder through a side feed port to mix with the melt. The extrusion temperature is 200-230°C, and the screw speed is 300-500rpm. After cooling, underwater pelletizing, drying and homogenization, a high-transmittance anti-aging glass fiber reinforced polypropylene composite material and a preparation method thereof are obtained.
[0036] This highly transparent and anti-aging glass fiber reinforced polypropylene composite material not only has excellent mechanical properties, but also has high light transmittance and weather resistance, and can be directly applied to light-transmitting parts in positions exposed to direct sunlight. The filling of glass fiber not only improves the shrinkage rate of polypropylene, but also significantly improves its mechanical properties. SEBS (styrene-ethylene-butylene-styrene block copolymer) can improve the spherulite size of polypropylene and has better transparency. In addition, styrene-ethylene-butylene-styrene has good compatibility with polypropylene, which improves the toughness of the material without affecting the transparency.
[0037] Nano zinc oxide is in the form of extremely fine particles, with an average particle size of nanometers, a large specific surface area, high surface activity, and good absorption and scattering ability for ultraviolet rays. The electrons in the valence band of nano zinc oxide can receive energy from ultraviolet rays to make transitions and absorb ultraviolet rays of a specific wavelength. In addition, the particle size of nano zinc oxide is much smaller than the wavelength of ultraviolet light, and the particles can scatter ultraviolet rays in different directions; at the same time, nano zinc oxide can fill the defects inside polypropylene and reduce the scattering points in the center of the material. However, there are many defects inside the nano zinc oxide grains, and more defects will still cause more scattering of light inside the material, affecting the transmission of light. By mixing with a small amount of nano titanium dioxide, trace nano titanium dioxide can cover the surface or internal defects of nano zinc oxide, and combine with the defect sites through physical or chemical effects, thereby modifying or passivating these defects, which has certain requirements for the particle size of the two. At the same time, due to the complementary particle sizes of the two, full mixing can reduce the internal defects and porosity of the material, improve the density and strength of the material, reduce light scattering, and increase the light transmittance. And the particle sizes of the two are smaller than visible light, and trace addition will not reduce the light transmittance of the material.
[0038] Nano zinc oxide and nano titanium dioxide have hydrophilic and oleophobic surfaces and are highly polar, and are often difficult to disperse well in organic media. Their dispersibility has a great influence on the light transmittance and light aging performance of the material. The present invention uses a silane coupling agent to modify the surface of the two. Silane coupling agent is a low-molecular organic silicon compound with a special structure, which can significantly improve the wetting state of inorganic fillers in polymer materials. The silane coupling agent can use the inorganic reactivity at one end to react with groups such as hydroxyl groups on the surface of nano zinc oxide to form a chemical bond; the organic functional group at the other end can react with the polymer, thereby enhancing the compatibility and bonding force between nano zinc oxide and the polymer, and improving its dispersibility in the polypropylene melt by converting the surface hydrophilic group into a hydrophobic group. DETAILED DESCRIPTION
[0039] The present invention is further described below by means of specific examples, which are only used to illustrate the present invention and do not limit the scope of the present invention.
[0040] Main raw material information in the present invention:
[0041] Homopolymer polypropylene Y26 was provided by Sinopec Zhenhai Refining and Chemical Company; MN18 was provided by Qingdao Refining and Chemical Company; random copolymer polypropylene M90 was provided by Sinopec (Tianjin) Petrochemical Company; glass fiber T438G was provided by Taishan Glass Fiber Company; the lubricant was commercially available calcium stearate, and nano titanium dioxide and nano zinc oxide were both commercially available;
[0042] Styrene-ethylene-butylene-styrene copolymer G1657 was provided by Kraton;
[0043] Polypropylene transparent nucleating agent NA-21 was provided by Japan Aidico; Millad NX800K was provided by Milliken;
[0044] Antioxidants 1010 and 168 were both provided by SI Group Chemicals; hindered amine light stabilizer UV944 was provided by BASF; triazine light stabilizer CYASORB UV-1164 was provided by Solvay; and maleic anhydride HW501 was provided by Huawen Company.
[0045] Examples A1-A3
[0046] The proportions of each component of the nano zinc oxide masterbatch of Examples A1-A3 are shown in Table 1, and the production steps are as follows:
[0047] (1) placing nano zinc oxide in a beaker, adding anhydrous ethanol and deionized water, breaking it up with ultrasound and stirring it for 1-2 hours, mixing it thoroughly, adding a silane coupling agent after the temperature is constant, washing the obtained solution, removing impurities by centrifugation, and drying it to obtain modified nano zinc oxide;
[0048] (2) weighing the modified nano zinc oxide, antioxidant and polypropylene obtained in step 1 according to the proportions in Table 1, mixing and stirring to obtain a premix 1;
[0049] (3) adding the premix 1 to a twin-screw extruder for melt mixing, the extrusion processing temperature is 180-210° C., the main engine speed is 300-600 rpm, and the nano zinc oxide masterbatch is obtained by melt blending and extrusion granulation;
[0050] Examples B1-B3
[0051] The proportions of each component of the nano titanium dioxide masterbatch of Examples B1-B3 are shown in Table 2, and the production steps are as follows:
[0052] (1) placing nano zinc oxide in a beaker, adding anhydrous ethanol and deionized water, breaking it up with ultrasound and stirring for 1-2 hours, mixing it thoroughly, adding a silane coupling agent after the temperature is constant, washing the obtained solution, removing impurities by centrifugation, and drying it to obtain modified nano titanium dioxide;
[0053] (2) Weighing, mixing and stirring the modified nano titanium dioxide, antioxidant and polypropylene according to the proportions in Table 2 to obtain premix 2;
[0054] (3) adding premix 2 to a twin-screw extruder for melt mixing at an extrusion processing temperature of 170 to 200° C. and a main engine speed of 300 to 600 rpm, and obtaining nano titanium dioxide masterbatch through melt blending and extrusion granulation;
[0055] Examples 1-8
[0056] The composition ratios of the components of the high-transmittance and anti-aging glass fiber reinforced polypropylene composite materials of Examples 1-8 are shown in Table 3, and the production steps are as follows:
[0057] (1) weigh nano zinc oxide masterbatch, nano titanium dioxide masterbatch, polypropylene, nucleating agent, maleic anhydride, antioxidant and other processing aids according to the proportions in Table 3, add them into a mixer, mix and stir to obtain premix 3;
[0058] (2) The premix 3 is added to the main feed port of the twin-screw extruder, and the glass fiber is fed through the side feed port of the twin-screw extruder. The extrusion processing temperature is 200-230° C., the main engine speed is 400-700 rpm, and the premix 3 is melt-blended and extruded into granules to obtain a reinforced polypropylene masterbatch.
[0059] The performance tests and test conditions of the high light transmittance and anti-aging glass fiber reinforced polypropylene composite materials obtained in the above Examples 1-8 and Comparative Examples 1-8 are as follows: the density is tested according to ISO 1183-1 standard, and the test condition is 23°C; the tensile strength is tested according to ISO 527-2 standard, the shape of the sample is a dumbbell-shaped sample, and the test speed is 50mm / min; the flexural strength and flexural modulus are tested according to ISO 178 standard, wherein the test speed is 2mm / min, the span is 64mm, and the sample size is 80mm×10mm×4mm; the cantilever beam notched impact is tested according to ISO 180 standard, and the sample size is 80mmX 10mm×4mm; the light transmittance is tested according to GB / T2410-2008 standard, and the sample wall thickness is 2.5mm; the xenon lamp aging is tested according to PV1303 standard, and the irradiation intensity is 60W / m 2 , and then test its light transmittance after 3 cycles of illumination experiment.
[0060] Table 1
[0061] raw material A1 A2 A3 Modified Nano Zinc Oxide 20 40 60 Antioxidant 1010 0.4 0.4 0.41 Antioxidant 168 0.4 0.4 0.4 Lubricants 1 1 1 Polypropylene 78.2 58.2 38.2
[0062] Table 2
[0063] raw material B1 B2 B3 B4 Modified nano titanium dioxide 1 (20~30nm) 5 10 15 Modified nano titanium dioxide 2 (10~20nm) 5 Antioxidant 1010 0.4 0.4 0.4 0.4 Antioxidant 168 0.4 0.4 0.4 0.4 Lubricants 1 1 1 1 Polypropylene 93.2 88.2 93.2 93.2
[0064] Table 3
[0065]
[0066]
[0067] Table 4
[0068]
[0069]
[0070] From the test results of Examples 1 and 2 and Comparative Example 1, it can be seen that high-crystalline homopolymer PP has higher crystallinity than ordinary homopolymer PP, and the crystal nucleus is relatively smaller, so the light transmittance is high; when random copolymer polypropylene is added to the system, the crystallization degree of the system will be reduced and the light transmittance will be improved.
[0071] From the test results of Example 2 and Comparative Example 2, it can be seen that nano zinc oxide and nano TiO2 can improve the light transmittance of the material. The crystal defects inside polypropylene will form scattering centers. When light passes through these defects, multiple reflections and refractions will occur, resulting in the inability of the light to pass smoothly, thereby affecting the transparency of the material. The surface effect of nano zinc oxide makes the interaction between its surface atoms and polypropylene molecules more intense. At the same time, its extremely small particle size can be distributed at the polypropylene lattice defects. This interaction helps to improve the defects and scattering centers inside the material and reduce the loss of light.
[0072] From the test results of Example 2 and Comparative Example 3, it can be seen that the transmittance of Example 2, which is a composite of nano zinc oxide and nano TiO2, reaches 46%, which is higher than the 43% of single nano zinc oxide, and the transmittance of Comparative Example 2 without adding nano fillers is only 38%. This is because there are also microporous defects on the surface of nano zinc oxide, and nano TiO2 can further optimize the internal defects of the material while modifying the surface of nano zinc oxide. At the same time, since the particle size of nano TiO2 (10-30nm) is smaller than the particle size of nano zinc dioxide (60-80nm), it is easier to penetrate into the interface defects between nano zinc oxide and polypropylene, thereby improving the light transmittance of the material.
[0073] In addition, from the light aging performance of Example 2 and Comparative Examples 2 and 3, it can be seen that the addition of nano zinc oxide and nano TiO2 keeps the light transmittance of the material at about 46% after aging, while the light transmittance of the material without nano zinc oxide and nano TiO2 after aging is 38%, indicating that nano zinc oxide and nano TiO2 can largely prevent the material from being damaged by ultraviolet light. This is because when exposed to ultraviolet light, the electrons on the valence bands of nano zinc oxide and nano TiO2 can absorb the energy of ultraviolet light and be excited to the conduction band, while generating hole-electron pairs, consuming the energy of ultraviolet light through the electron transition process, thereby achieving the absorption of ultraviolet light. Nano zinc oxide has a strong absorption capacity for long-wave UVA, and nano titanium dioxide has a stronger absorption effect on medium-wave UVB. The synergistic effect of the two can absorb ultraviolet light with a wider wavelength range, thereby improving the material's anti-light aging performance.
[0074] From the test performance of Examples 2, 3 and 4, it can be seen that when the content of nano-TiO2 is constant, as the content of nano-zinc oxide increases, the material transmittance first increases and then decreases, and the optimal addition amount is 4%. Nano-zinc dioxide can optimize the internal defects of the material. When the addition amount is small, the internal structure of polypropylene can be optimized. When the addition amount is large, nano-zinc oxide is prone to uneven dispersion and agglomeration points appear, which has an adverse effect on the material transmittance and performance.
[0075] It can be seen from the test results of Example 3 and Comparative Examples 4 and 5 that when nano-TiO2 is added in trace amounts, it can cooperate with nano-zinc oxide to improve the transmittance of the material. At this time, nano-TiO2 is evenly dispersed in the internal defects of polypropylene, and plays a role in system regulation and control defects with nano-zinc oxide; when the amount of nano-TiO2 added gradually increases, the difficulty of dispersion increases, and the agglomeration effect increases the dispersed particle size of nano-TiO2 in the material, and the transmittance decreases; and the excess nano-TiO2 that does not fill the system defects is more easily distributed in the interface of polypropylene and glass fiber due to its small particle size and strong penetration, affecting the combination between the two and reducing the material performance. It can be seen from the test results of Examples 3, 5 and Comparative Example 7 that adding a nucleating agent to the system can accelerate the crystallization rate, refine the crystal ball size, reduce the scattering and refraction of light on the spherulite interface, thereby improving the transparency of polypropylene. Among them, Example 7 uses a nucleating agent compound, and the performance and transmittance are improved under the synergistic effect of NA-21 and NX800K. Comparative Example 2 does not add nanofillers, but its performance is similar to that of Comparative Example 6 without nucleating agent, because the particle size of nano zinc oxide and nano TiO2 is small, and they can also play a role of heterogeneous nucleation in polypropylene. However, compared with the nucleating agent, the crystallization rate of nanofillers is slow and the crystal nucleus size is large, so the light transmittance of Comparative Example 2 is slightly higher than that of Comparative Example 6, indicating that nano zinc oxide and nano TiO2 can replace a certain proportion of nucleating agents to reduce costs.
[0076] From the test results of Example 3 and Comparative Example 6, it can be seen that when the added content is the same, the transmittance of Example 3 is maintained at 52%, while the transmittance of Comparative Example 6 is only 48%, indicating that the nano-TiO2 with a particle size of 20-30nm in Example 3 and the nano-zinc oxide particle size selected in this experiment have the best synergistic effect, and although the nano-TiO2 with a particle size of 10-20nm is smaller, its effect on penetrating internal defects of polypropylene and filling surface gaps of nano-zinc oxide is weaker than that of 20-30nm particle size.
[0077] From the test results of Examples 3, 6 and Comparative Example 7, it can be seen that different light stabilizers have no obvious effect on material properties and transmittance. The transmittance of Comparative Example 8, which does not add light stabilizers, drops sharply after xenon lamp aging, while the transmittance of the hindered amine-triazine compounded ultraviolet absorber in Example 6 remains at 48% after xenon lamp aging. This shows that the anti-light aging effect of a single hindered amine ultraviolet absorber is lower than that of a hindered amine-triazine compounded ultraviolet absorber. Hindered amine ultraviolet absorbers avoid oxidative damage to materials by capturing free radicals, while triazine ultraviolet absorbers directly absorb ultraviolet rays and convert their energy. This compounding method can achieve comprehensive protection against ultraviolet rays and improve the overall light stability of the material. The transmittance of Comparative Example 7, which does not add light stabilizers, is only 39% after aging, which is similar to the difference in transmittance before and after light aging of Comparative Examples 2 and 3, indicating that nano zinc oxide and nano TiO2 can replace part of the role of light stabilizers.
[0078] From the test results of Examples 5 and 7, it can be seen that the light transmittance retention rate of Example 7 before and after aging is better than that of Example 5. After the hindered amine ultraviolet absorber reacts with light-activated hydrogen peroxide, it will produce hydroxylamine with strong hydrogen donation ability, which can terminate the chain growth of various free radicals. With the ability of nano zinc oxide and nano TiO2 to scatter internal ultraviolet rays, it can; the triazine ultraviolet absorber absorbs ultraviolet rays and converts them into harmless energy release, while the ultraviolet energy scattered by nano zinc oxide and nano TiO2 is also gathered inside the material, which cannot effectively prevent the chain growth of the reaction and can only slow down the aging degradation rate. It shows that the hindered amine ultraviolet absorber is better than the triazine ultraviolet absorber in the nano zinc oxide and nano TiO2 system.
[0079] The specific scheme described above is a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. For those skilled in the art, any modification, replacement, supplement, optimization, etc. made within the spirit and principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A high light transmittance and anti-aging glass fiber reinforced polypropylene composite material, characterized in that: The invention is prepared from the following raw materials in percentage by mass: 20-60% of polypropylene, 10-15% of toughening agent, 5-20% of glass fiber, 0.3-1% of nucleating agent, 10-20% of modified nano zinc oxide masterbatch, 5-20% of modified nano titanium dioxide masterbatch, 0.01-0.5% of light stabilizer, 0.01-0.5% of antioxidant and 1-5% of other auxiliary agents.
2. The high light transmittance and anti-aging glass fiber reinforced polypropylene composite material according to claim 1, characterized in that: The PP resin is one or more of homopolymer polypropylene and random copolymer polypropylene.
3. The high light transmittance and anti-aging glass fiber reinforced polypropylene composite material according to claim 1, characterized in that: The toughening agent is a transparent styrene-butadiene copolymer.
4. The high light transmittance and anti-aging glass fiber reinforced polypropylene composite material according to claim 1, characterized in that: The glass fiber is alkali-free chopped glass fiber treated with a silane coupling agent, with a chopped length of 3 to 4.5 mm and a diameter of 7 to 15 um.
5. The high light transmittance and anti-aging glass fiber reinforced polypropylene composite material according to claim 1, characterized in that: The lubricant is a stearate, such as one or a combination of magnesium stearate, zinc stearate, calcium stearate, and vinyl bisstearamide.
6. The high light transmittance and anti-aging glass fiber reinforced polypropylene composite material according to claim 1, characterized in that: The antioxidant is a hindered phenol and phosphite composite antioxidant.
7. The high light transmittance and anti-aging glass fiber reinforced polypropylene composite material according to claim 1, characterized in that: The nucleating agent is one or more α-nucleating agents.
8. The high light transmittance and anti-aging glass fiber reinforced polypropylene composite material according to claim 1, characterized in that: The ultraviolet stabilizer is one or more of hindered amine and triazine ultraviolet absorbers.
9. The high light transmittance and anti-aging glass fiber reinforced polypropylene composite material according to claim 1, characterized in that: The modified nano zinc oxide masterbatch includes the following raw materials in parts by weight: Modified nano zinc oxide: 20-60wt%; Lubricant: 0.1-2wt%; Antioxidant: 0.01-0.5wt%; Polypropylene: remaining components; The production steps of the nano zinc oxide masterbatch are as follows: The modified nano zinc oxide, lubricant and polypropylene are weighed according to the above mass ratio, and the weighed materials are put into a high-speed mixer for uniform mixing; melt extruded by a twin-screw extruder, pelletized underwater and dried to obtain nano zinc oxide masterbatch. The temperature of each zone of the twin-screw extruder is 200-230°C, and the main engine speed is 300-400rpm.
10. The high light transmittance and anti-aging glass fiber reinforced polypropylene composite material according to claim 9, characterized in that: The particle size of the nano zinc oxide is between 60 and 80 nm.
11. The high light transmittance and anti-aging glass fiber reinforced polypropylene composite material according to claim 1, characterized in that: The modified nano titanium dioxide masterbatch includes the following raw materials in parts by weight: Nano titanium dioxide: 5-15wt%; Lubricant: 0.1-2wt%; Antioxidant: 0.01-0.5wt%; Polypropylene: remaining components; The modified nano titanium dioxide masterbatch modification steps are as follows: Nano-titanium dioxide was placed in a mixed solution of anhydrous ethanol and deionized water (2:3), and after ultrasonication, it was stirred with a magnetic stirrer for 1 hour at a speed of 1000 r / min. After the temperature was constant, a silane coupling agent (5%-10%) was gradually added dropwise. After the reaction was completed, the solution was washed, centrifuged to remove impurities, and dried to obtain modified nano-titanium dioxide.
12. The high light transmittance and anti-aging glass fiber reinforced polypropylene composite material according to claim 11, characterized in that: The particle size of the nano titanium dioxide is between 10 and 30 nm.
13. The method for preparing the high-transmittance and anti-aging glass fiber reinforced polypropylene composite material according to any one of claims 1 to 12, characterized in that: The production steps are as follows: (1) weighing nano zinc oxide masterbatch, nano titanium dioxide masterbatch, polypropylene, nucleating agent, maleic anhydride, antioxidant and other processing aids according to the proportion of claim 1, adding them into a mixer and mixing them evenly; (2) The premix is added into a twin-screw extruder from the main feed port, and the glass fiber is fed into the twin-screw extruder through the side feed port. The extrusion processing temperature is 200-230° C., and the main engine speed is 400-700 rpm. After melt blending, extrusion, underwater pelletizing, drying and homogenization, a high-transmittance and anti-aging glass fiber reinforced polypropylene composite material and its preparation method are obtained.
Citation Information
Patent Citations
Low-density, high-transmittance polypropylene material resistant to long-term thermo-oxidative aging and its preparation method
CN112430363B
Light-transmitting polypropylene compound as well as preparation method and application thereof
CN117801419A
Low-odor and low-VOC (Volatile Organic Compounds) glass fiber reinforced polypropylene composite material and preparation method thereof
CN103342859A
Anti-aging high-transparency high-strength polypropylene plastic barrel and preparation method thereof
CN109705473A
High-haze and high-transmittance polypropylene composition as well as preparation method and application thereof
CN114854136A
Cited By
Polypropylene light-transmitting material as well as preparation method and application thereof
CN120464068A